Charcot-Marie-Tooth disease and posterior scleritis: a case report - Martins, Elisabeth N. [UNIFESP] (2000)
Purpose: To describe the unusual association of Charcot-Marie-Tooth disease (CMTD) and posterior scleritis. Methods: Case report of a 16-year-old female with decreased visual acuity and pain in both eyes. Results: Ophthalmologic examination showed a posterior scleritis, confirmed by ultrasound and angiofluoresceinography. Foot deformities and sensory dysfunction were identified in the patient and some of her relatives. The diagnosis of CMTD in this patient was confirmed by eletrophysiologic studies. Conclusions: The association of posterior scleritis in a patient with CMTD has never been reported. This is also the first description of an inflammatory ocular disease in these patients.